Phase 2 study of LY3023414 in patients with advanced endometrial cancer harboring activating mutations in the PI3K pathway. Issue 6 (27th December 2019) - Rubinstein, Maria M.; Hyman, David M.; Caird, Imogen; Won, Helen; Soldan, Krysten; Seier, Kenneth; Iasonos, Alexia; Tew, William P.; O'Cearbhaill, Roisin E.; Grisham, Rachel N.; Hensley, Martee L.; Troso‐Sandoval, Tiffany; et al.
Abstract : Background: PI3K pathway activation is common in endometrial cancer. We evaluated the safety and efficacy of the dual PI3K/mTOR inhibitor, LY3023414, in patients with advanced endometrial cancer harboring activating mutations in the PI3K pathway. Methods: We conducted a single‐arm phase 2 study of monotherapy LY3023414. Eligible patients had advanced endometrial cancer of any grade, prior management with 1‐4 cytotoxic lines, and PI3K pathway activation prospectively defined as a loss‐of‐function PTEN alteration or activating alteration in PIK3CA, AKT1, PIK3R1, PIK3R2, or MTOR . The primary objective was best overall response rate (ORR) per RECIST 1.1. Results: Twenty‐eight patients were treated; histologies included endometroid (39%), carcinosarcoma (25%), serous (21%), and mixed (14%). Patients were heavily pretreated, with a median of 2 prior cytotoxic lines (range, 1‐3). The most common alterations involved PIK3CA (68%), PTEN (43%), and PIK3R1 (32%). In the 25 efficacy‐evaluable patients, the ORR was 16% (90% CI, 7%‐100%), and the clinical benefit rate was 28% (90% CI, 16%‐100%). Four patients had a confirmed partial response, and 2 responses lasted for >9 months. The median progression‐free survival and overall survival were 2.5 months (95% CI, 1.2‐3.0) and 9.2 months (95% CI, 5.0‐15.9), respectively. The most common all‐grade treatment‐related adverse events were anemia (71%), hyperglycemia (71%), hypoalbuminemia (68%), and hypophosphatemia (61%). No correlation between molecular alterations and response was observed. Conclusion: In patients with heavily pretreated advanced endometrial cancer prospectively selected for tumors with activating PI3K pathway mutations, LY3023414 demonstrated modest single‐agent activity and a manageable safety profile. Abstract : The authors conducted a single‐arm phase 2 study of LY3023414, a dual PI3K/mTOR inhibitor, in patients with advanced endometrial cancer who were prospectively selected to have activating PI3K pathway mutations. LY3023414 was tolerable and had a modest clinical response (overall response rate, 16% [90% CI, 7%‐100%]).